Assessing Regional Integration in Africa VIII - United Nations (United Nations, 2017)
The African Continental Free Trade Area (CFTA) promises to give a significant boost to the continent’s economy and, in particular, to support industrialization and structural transformation. In this context, the 8th edition of Assessing Regional Integration in Africa (ARIA VIII) looks at what will be needed to ensure that the CFTA is implemented and that iintra-African trade plays a more dynamic role in contributing to economic transformation in Africa. Drawing on political economy analysis, the report analyses what kind of institutional set-up will be needed to ensure the CFTA’s implementation as well as the capacity development needs at the national, regional economic community and continental levels. The report also provides an update on the expected benefits of the CFTA’s implementation, as well as the usual chapter on the status of regional integration in Africa.